Growth Response of Cocoa Seedlings (Theobroma cacao L.) in several Combinations of Planting Media and Trichoderma sp. as Biological Fertilizer - Erfandari, Ovy; Azis, Abdul; Nurmayanti , Sri; Sudirman, Albertus; Sahara, Ella (Jurnal Biologi Tropis, 2024)
Indonesia is the third largest cocoa (Theobroma cacao L.) producing country in the world. In 2019 cocoa production in Lampung was 58,852 tons with a plantation area of 79,356 ha, in 2020 it was 58,623 tons with an area of 79,469 ha and in 2021 58,414 tons with an area of 77,174 ha. One of the reasons for this decline in production is plant pest organisms (OPT), namely fruit rot disease caused by the pathogen Pytophthora palmivora. Use of Trichoderma sp. can increase plant resistance and growth and act as a biological controller outside and inside the soil. The research was carried out on the grounds of the Lampung State Polytechnic from August to November 2023. This research aims to determine the effect of planting media and administration of Trichoderma sp. on the growth of cocoa seedlings. The method used was a Randomized Block Design (RAK) with 4 treatments and 4 replications so that there were 16 experimental units. Treatment P0 consisted of: Top Soil (Control), P1 Top Soil + Compost Fertilizer (2:1), P2 Top Soil + Trichoderma sp. (50:1), P3 Top Soil + Compost + Trichoderma sp. (50:25:1). The results of the research on treatments P3, P2 and P1 affected plant height, number of leaves and stem diameter. The P3 treatment showed the best results for the variables plant height 39.50 cm, number of leaves 21.58 and leaf area 37.79 cm2. Treatment P2 showed the best results for the stem diameter variable of 0.66 cm.